Physical activity and fruit and vegetable consumption during the COVID-19 pandemic for people with type 2 diabetes mellitus. Issue 5 (October 2022) - Andersen, Jennifer A.; Willis, Don E.; Hallgren, Emily; McElfish, Pearl A.; Felix, Holly C.
Abstract: Aims: To understand the associations between sociodemographic factors, self-rated health, and COVID-19-related changes in physical activity and diet and the reported number of days per week participants engaged in physical activity and consumed fruits and vegetables for people with type 2 diabetes mellitus (T2DM). Methods: Respondents from Arkansas primary care clinics completed a survey between October 2020 and January 2021. Multivariable regression determined associations between sociodemographic factors, self-rated health, and COVID-19-related changes in physical activity and diet and the reported number of days per week participants engaged in physical activity and consumed fruits and vegetables. Results: Respondents exercised for at least 30 min on a mean of 2.09 days and consumed five or more fruit and vegetable servings on a mean of 3.57 days. Males engaged in one additional day of physical activity compared to women. Respondents with a college degree or higher ate 5 or more fruit and vegetable servings on fewer days per week than those with a high school education or less. Conclusions: Results reaffirm a need for diabetes education programs and health care providers to provide information on the importance of maintaining physical activity and a healthy diet as part of a self-care plan for T2DM, especially during public health emergencies like the COVID-19 pandemic. Highlights: Individuals with T2DM experienced physical activity and diet changes amid COVID-19. Respondents exercised for at least 30 min on a mean of 2.09 days. Respondents consumed 5 or more fruit and vegetable servings on a mean of 3.57 days. Males engaged in one additional day of physical activity compared to women. Self-rated health was associated with numbers of days engaged in physical activity.